SOCIOLINGUISTIC DIVERSITY IN ENGLISH LANGUAGE EDUCATION: INSIGHTS FROM A MULTILINGUAL CLASSROOM IN KARAKALPAKSTAN: SOCIOLINGUISTIC DIVERSITY IN ENGLISH LANGUAGE EDUCATION: INSIGHTS FROM A MULTILINGUAL CLASSROOM IN KARAKALPAKSTAN - Madaminova, Nilufar (Журнал иностранных языков и лингвистики, 2025)
Understanding the sociolinguistic profile of a classroom is critical for designing effective language education programs in multilingual contexts. Such profiles reveal the interplay of linguistic, cultural, and social factors that shape language learning experiences [2]. This study examines English language education in a 6th-grade classroom in Ellikkal’a, Karakalpakstan, a region marked by linguistic diversity and ethnic heterogeneity. Students in this setting navigate multiple languages, including Karakalpak, Uzbek, Russian, and Kazakh, while learning English as a foreign language. This article analyzes the sociolinguistic characteristics of this learning environment, identifies challenges and opportunities for English acquisition, and proposes pedagogical and assessment strategies to foster inclusive education applicable to similar multilingual contexts